Long-term summer warming trend during the Holocene in central Asia indicated by alpine peat α-cellulose δ13C record. (1st January 2019) - Rao, Zhiguo; Huang, Chao; Xie, Luhua; Shi, Fuxi; Zhao, Yan; Cao, Jiantao; Gou, Xiaohua; Chen, Jianhui; Chen, Fahu
Abstract: The long-term cooling or warming trend is one of the most important aspects of Holocene paleoclimatic research. However, there are currently significant discrepancies among climatic simulation results, sedimentary and synthesized Holocene temperature records. These discrepancies call for new Holocene temperature records with a robust chronology and unambiguous indicative significance. Here, we present a ca. 45-year-resolution alpine peat α-cellulose carbon isotopic (δ 13 C) record from the Altai Mountains in central Asia. The chronology of the record has been well-constrained by 22 AMS 14 C dates of the peat α-cellulose samples. Based on detailed modern-process study results, the indicative significance of the record has been carefully determined as summer temperature indicator. The record reveals an overall trend of increasing summer temperature for the past ca. 11 ka with a warmer early (from ca. 8–6 ka BP) and late (from ca. 4–0 ka BP) Holocene and colder middle Holocene (from ca. 6–4 ka BP). The general pattern of a warmer early and late Holocene and colder middle Holocene is consistent with previously reported temperature records from central Asia, the Tibetan Plateau, and North China. The long-term warming trend in our summer temperature record is consistent with recently reported winter temperature records from high latitudes of continental Eurasia. All these results further support the reliability of our summer temperature record from central Asia. The better understandings about the Holocene temperature history and its possible driven mechanism(s) can be benefited potentially from more reliable Holocene temperature records, including our record reported in this paper. Highlights: The well-dated high-resolution alpine peat α-cellulose δ 13 C record from central Asia. The reported peat α-cellulose δ 13 C dataset is an indicator of summer temperature. The long-term Holocene summer warming trend in the peat α-cellulose δ 13 C record. The GHG forcing as the most plausible driving for the long-term Holocene warming.